Lixiviación de nitratos a partir de fertilizantes y biosólidos en un suelo arcilloso - Rimski-korsakov, Helena (2000)
Leaching of fertilizers is one of the main reasons of nitrate concentration increases in underground waters. We studied the effect of fertilizers and biosolids on nitrate accumulation in soil depth. We determined nitrates at different depths of a beheaded Vertic Argiudoll, near La Plata city. The application of biosolids in high doses (equivalent to 200 Mg ha-1(wet weight basis) for one year, showed significant nitrate accumulation at soil depth in relation to the check. The application of mineral fertilizers and biosolids in doses equivalent to 25 Mg ha-1 (wet weight basis) for three successive years showed lower risk of nitrate leaching. A plot fertirrigated (soluble fertilizers) showed high nitrate accumulation in soil depth and then high contamination risk. The clayey soil texture did not limit the risk of nitrate leaching.